2008
DOI: 10.1002/ptr.2487
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nigella sativa and a number of its antioxidant constituents towards azoxymethane‐induced genotoxic effects and colon cancer in rats

Abstract: This study examined the chemopreventive effect of Nigella sativa and some of its antioxidant constituents on a number of colon cancer biomarkers in rats induced with azoxymethane (AOM). Sixty male Sprague-Dawley rats were randomly assigned into ten subgroups: vehicle (1-5) and experimental (6-10). The rats in each group were fed one of the following diets: basal diet, (200 mg/kg) Nigella sativa, (0.2 mg/kg) selenium, (1.2 mg/kg) all-trans-retinol plus (100 mg/kg) DL-alpha-tocopherol and (10 mg/kg) thymoquinone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 70 publications
(69 reference statements)
1
24
0
Order By: Relevance
“…In another study, Al-Johar et al (21) reported modulation by TQ of aberrant crypt foci in rats induced by azoxymethane.…”
Section: Secondary Targets Of Tqmentioning
confidence: 95%
See 1 more Smart Citation
“…In another study, Al-Johar et al (21) reported modulation by TQ of aberrant crypt foci in rats induced by azoxymethane.…”
Section: Secondary Targets Of Tqmentioning
confidence: 95%
“…Thus far, studies cited in the literature have suggested that TQ protects the kidney against ifosfamide, mercuric chloride, cisplatin, and doxorubicin-induced damage by preventing renal GSH depletion and antilipid peroxidation product accumulation, thereby improving renal functioning (1820). TQ supplementation in diet of Sprague-Dawley rats inhibited malonaldehyde content in liver, which suggests reduction in the lipid peroxide formation (21). Furthermore, TQ ameliorated hepatotoxicity of carbon tetrachloride as seen by the significant reduction of the elevated levels of serum enzymes and significant increase of the hepatic GSH content (2224).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Our previous study [65] showed that selenium is one of the constituents of basal diet (0.223±0.009 µg/g) fed to experimental animals in our institution. Even though, selenium was not measured in this study, we should take into consideration the possible interaction role of mercury-selenium in the accumulations and the selenium antagonistic effect on the toxic effect of mercury on ovary or other tissues.…”
Section: Mean Mercury Content (Ng/g) In Ovary Tissuesmentioning
confidence: 99%
“…studies, from which hypotension (Khattab & Nagi, 2007;Dehkordi & Kamkhah, 2008), hypoglycemic (Kaleem et al, 2006;Meddah et al, 2009), hypolipidemic (Bamosa, Ali, & Al-Hawsawi, 2002), antioxidant (Uz et al, 2008;Kanter, Coskum, & Uysal, 2006) anti-inflammatory (Al-Ghamdi, 2001) and anti-tumor (Mbarek, 2007;Al-Johar, 2008) effects can be noted. It is also used as diuretic, anti-parasitic and carminative agent (Ali & Blunden, 2003).…”
Section: Discussionmentioning
confidence: 99%